Outdoor (1→3)-β--glucan Levels and Related Climatic Factors - Sung Ho Hwang; Chung Sik Yoon; Jae Bum Park (Korean Society for Preventive Medicine, 2014)
ObjectivesTo evaluate the monthly variation in the airborne (1→3)-β-D-glucan level throughout one year and its relationship with climatic factors (temperature, relative humidity, wind speed, hours of daylight, cloud cover, and pollen counts).MethodsA total of 106 samples were collected using a two-stage cyclone sampler at five outdoor sampling locations (on top of 5 university buildings). The kinetic limulus amebocyte lysate assay was used to obtain (1→3)-β-D-glucan levels.ResultsAirborne (1→3)-β-D-glucan levels were significantly higher in the spring, particularly in April, and temperature was significantly related to (1→3)-β-D-glucan levels (r =0.339, p<0.05).Conclusions(1→3)-β-D-glucan levels may be highest in the spring, and outdoor temperature may influence (1→3)-β-D-glucan levels.